REPOSITION OF WIDOW BY DEATH DIVORCE IN BATAKNESSE INHERITANCE LAW FROM GENDER PERSPECTIVE - Amri Panahatan Sihotang (Fakultas Hukum, Universitas Diponegoro, 2018)
This journal is to study the reposition of widow in traditional Batak’s hereditary law by using gender approach. The Batak’s hereditary Law, tends to be referring to patrilineal kinship which is determined from the line of father’s or husband’s descent so the Widow is not the beneficiary of the husband but the son in the Batak’s ethnic and culture. Along with the current development and important role of a mother/woman in family life, it is important to re-study more deeply the position of a widow in Batak’s hereditary law and some related theories which one of themis gender approach .This is considerably important because there are some modern thinker related to customary law who intend to renew the law especially the beneficiary for the sake of gender equality in the current ages by bilaterally repositioning widow to the national hereditary law . By Educating Batak’s hereditary law from gender perspective, the Batak’s ethic will be able to critically think and flexibly find solution to share the property by positioning the widow as the beneficiary or the heir.